Yeast cell wall preparation from Saccharomyces cerevisiae enhances immune effector cells of Indian major carp, Catla catla (Hamilton) - Pal, Devonita; Joardar, Siddhartha N; Roy, Barun (Indian Journal of Fisheries, 2011)
The present study was designed to assess the effect of oral administration of yeast cell wall (YCW) preparation from Saccharomyces cerevisiae on non-specific immune responses of catla, Catla catla (Ham.). Fish fed with experimental diet (for 15 days) were switched back to control diet and fed for a period of 30 days. Non-specific immune responses, viz., superoxide anion production, phagocytosis, nitrite production and proliferation of leukocytes along with haematological parameters were assessed at 10 days interval during post YCW feeding period. Although there was no significant difference in mean haematocrit values, dynamic changes of differential leucocyte count was observed in treated group as compared to control. Superoxide anion production, in vitro phagocytic activity and nitrite production of leucocytes increased significantly (p<0.01) and reached peak on 10th day post-treatment. In vitro lymphocyte proliferation also showed similar trend throughout the experimental period. The results showed that supplementation of YCW preparation in feed for 15 days had significant immunostimulatory effect on C. catla